Transformational Leadership of School Administrators in the New Normal Era under the Sa Kaeo Provincial Administrative Organization - Chansawat, Komsan; Suwansumrit, Chalabhorn (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
The objectives of this research were to 1) study the level of the transformational leadership of school administrators in the New Normal Era under Sa Kaeo Provincial Administrative Organization, 2) compare opinions averages of the school administrators and teachers about transformational leadership of school administrators in the new normal era classified by gender, educational level, position, work experience, and school sizes, and 3) study the guidelines for developing transformational leadership of school administrators in the new normal era. The sample from stratified random sampling by school sizes consisted of 272 school administrators and teachers. The research instrument was a questionnaire with a validity (IOC values) between 0.67-1.00 and a reliability value of 0.87. The data were statistically analyzed by using percentage, mean, standard deviation, t-test, One-way ANOVA, LSD, and content analysis. The results of the research were as follows: 1) the level of transformational leadership of school administrators in the new normal era was at a high level in overall, and particular aspects, ranking from the highest to the lowest mean: individualized consideration, inspirational motivation, idealized influence, and intellectual stimulation properly, 2) opinions of school administrators and teachers on transformational leadership of school administrators in the new normal era, classified by gender did not have a difference, but the opinions were classified by education level, position, work experience, and different school sizes with a statistically significant at .05 level, and 3) the developed guidelines of transformational leadership of school administrators in the new normal should be trained of using technology in schools to solve online teaching and learning management problems in the epidemic situation of COVID-19.